Key technology of data center network for cloud network convergence - Jianglong WANG; Bo LEI; Yunpeng XIE; Qi HE; Yunhe LI (Dianxin kexue)
“New infrastructure” brings new opportunities for the development of data centers.Data center has become an important part of the operator’s cloud-network convergence infrastructure,providing a strong technical foundation for innovative applications in the 5G + AI era.The new requirements of the data center network in the cloud network convergence background were analyzed.The key technologies in ultra-large-scale networking,ultra-low latency lossless network,and unified service end-to-end bearer were given.Finally,a large-scale cloud data center networking solution were presented,and the key technologies were verified.